The Relationship between Foreign Direct Investment, Electricity Consumption and Economic Growth in Vietnam - Long, Pham Dinh; Ngoc, Bui Hoang; My, Duong Tien Ha (International Journal of Energy Economics and Policy, 2018)
One of the prerequisites for the successful implementation of national industrialization and modernization is the synchronous development of fundamental industries. Electricity is a key industry that determines the success of other industries. The main purpose of this paper is to investigate the causal relationship between electricity consumption, foreign direct investment and economic growth in Vietnam during the period 1990-2015, by using Toda-Yamamoto approach and autoregressive distributed lag (ARDL) approach. The empirical results show strong statistical evidence that electricity consumption and foreign direct investment have positive impacts on economic growth in Vietnam in both short term and long term. Keywords: FDI, electricity consumption, economic growth, Vietnam. JEL Classifications: F21; F43; Q43